Scientific, Ethical, and Economic Aspects of Farm Animal Welfare - Croney, Candace; Mench, Joy; Muir, William; Anthony, Raymond; Golab, Gail; Hofacre, Charles; Hulet, Michael; Johnson, Anna K.; Lusk, Jayson L.; Widmar, Nicole Olynk; Schinckel, Allan P.; Shearer, Jan; et al. (Council for Agricultural Science and Technology (CAST), 2018)
Many conflicting values and norms in our society related to the use of animals lead to increasing disagreements about what constitutes a “good life” for the animals in our care. Broadly speaking, applied ethicists have discussed two different approaches to this topic—one focuses on the consequences of using animals in particular ways, and the other on the morality of that use, regardless of the consequences. These two positions are reflected in the “animal welfare” and “animal rights” views, respectively. Another ethical perspective is that animals are owed a good standard of care because of the benefits we derive from them. Nevertheless, understanding both the science and the ethics of animal welfare is critical to understanding and reconciling differing perspectives about animal care and use. This task force report addresses the issue by examining these key topics: the current issues facing agricultural animal production, insights into the origins of current welfare concerns, major scientific advances that have occurred since the 1997 CAST Task Force Report, and outstanding challenges and priority areas for future research, coordination, and outreach relative to agricultural animal welfare.
Keywords: Animal Welfare; Animal Ethics